THE EFFECT OF GOVERNMENT REVENUE AND EXPENDITURE ON ECONOMIC GROWTH - Mely Novita Sari; Hadi Sasana (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study leads to an analysis of the relationship between exports, imports, and central government spending on the growth of the Indonesian economy. In this study, we selected periodic data throughout 1990-2020 obtained from the World Bank and Financial Notes. The ECM (Error Correction Model) analysis method is used in this study. Then tested using the stationary test, cointegration test, and the classical assumption test. This study obtained the results that export and import variables have an influence on economic growth in the short term, while central government spending has an influence on economic growth in the long term. Therefore, the researcher concludes that better government involvement in economic growth is needed for the economy to function smoothly. To avoid a negative trade balance, the government must be able to control both exports and imports, as well as budgetary spending. In this situation, the government is viewed as a policymaker and a state stakeholder, and it is hoped that it will make sound policy decisions that will benefit Indonesia's economy.